Health and Lifestyle Practices of Under Graduate Students Studying in Selected Nursing College - Anagha.M1 , Ritu Gaikwad1 , Ronald Masumba1 , Kraus1 , Asha Varghese1 , Deepak Sethi,2 Merlin Suji3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Life styles of the people is decided as early in early childhood period. School and family practices areessential in deciding healthy and lifestyle practices in adulthood. Sometimes, peer pressure changes theindividuals’ lifestyles. The study aimed to assess the healthy and lifestyles practices of undergraduate studentsstudying in selected nursing college. Methodology: A Non-Experimental Descriptive Research approachused in various nursing colleges in Pune city. The selection of the sample was based on easy geographicalaccessibility, cooperation and availability of samples .The sample size for the study was 96,selected byusing non probability convenience sampling technique who met the inclusion criteria. A self-structuredquestionnaire was developed based on the research problem, to get the information from the samples.Result : As for the nutrition the mean score is 48. 64% of adolescents replied that they will avoid half cookedfood, 56% replied they avoid fast foods and 59% replied they prefer healthy eating.91% replied that theydon’t have any problem in paying attention. 75% doesn’t have any problem for sleep. 62% replied that theyhave troubles in relaxing and 44 % replied they usually get into the arguments. 55% involved in activitieslike sports, games and dance. 70% feels healthy and 68% have complaints of stomachaches, headaches, orother aches and pains. 96% have no problems in handling life. Around 93 % satisfied with their family .Around 93% have the support with the family and friends. 57.29 % replied that they don’t have computer intheir home. 61.46 % students live with their parents. 96.88% has personal mobile. 73% regularly visit socialnetworking sites. 96% of adolescents wash their hands before eating foods and 83% wash their hands withsoap or hand wash. 16.67% have habits of cigarettes/chewing Pan/Guthka but 945 aware about the harmfuleffects of smoking. 13% replied they tried alcohol but they believe that 41% of their friends has alcoholdrinking habits. 86% students feel getting good score in college is important to family. 94% feel safe incollege and only 4% says that their behavior influenced by peer pressure. Others 96% doesn’t agree with it.Conclusion: Diet practices, concentration in work , family connectedness scored less compared to othercomponents. Very few students have the habits of alcohol, smoking etc. Personal hygiene was practiced wellin adolescents. Decision is taken by themselves more than the peer pressure. Majority of the adolescentsknows the important of their education and they feel safe and good in college.